Socio-demographic, economic and health profile of adults with sickle-cell disease - Júlia Lamese Amaral; Nívea Aparecida Almeida; Paula Silveira Santos; Patrícia Peres de Oliveira; Patrícia Peres de Oliveira (Universidade Federal do Ceará, 2015)
Objective: to describe socio-demographic and economic characteristics, lifestyle, clinical manifestations, use of medications and monitoring of adults with sickle-cell disease. Methods: a descriptive study with quantitative approach, made with 20 adults, registered in a Hematology and Hemotherapy Center, using, for data collection, interviews in the participant's home and medical records. In order to have the database, the EpiDatae analysis software through statistical program was used. Results: most of the population consisted of women, married, with complete high school, which used exclusively the Unified Health System. The average age was 30.6 years, and 90.0% (95% CI 68.3-98.8) were black. All of them reported painful crises and fatigue. They used folic acid daily 35.0% (95% CI 15.4-59.2). Conclusion: the implications of sickle-cell disease could be mitigated through primary, secondary and tertiary health care, according to the needs of those adults.